Determination of the ratio of pulmonary blood flow to systemic blood flow by derivation of amplitude weighted mean velocity from continuous wave Doppler spectra. Issue 2 (February 1989) - Jenni, R; Ritter, M; Vieli, A; Hirzel, H O; Schmid, E R; Grimm, J; Turina, M
Abstract : Conventional Doppler echocardiographic techniques for the estimation of blood flow ratios depend on the precise measurement of the diameters of the aorta and the pulmonary artery and the mean blood flow velocities in these vessels. A simpler and quicker method is described, based on the calculation of the systolic time integrals of the amplitude weighted mean velocities from continuous wave Doppler spectra within the great arteries. In 30 controls the mean (2 SD) ratio of pulmonary to systemic blood flow averaged 0.952 (0.085). The results of the new technique showed a good agreement with those of quantitative dye dilution and oximetry in 16 patients with intracardiac left to right shunts.